Inclusive Institutional Environment as an Important Factor of Sustainable Development of the Economy and Business - Kamilova N. A.; Nasimov I. X. (International Journal on Economics, Finance and Sustainable Development, 2021)
In the work was analyzed the entity of institutions, based on the study have been substantiated, the role of inclusive institutions in the long-term and high-quality growth of the economy and entrepreneurship. Also described the successful practices of institutional reforms in foreign countries, as well as the main aspects of the strategy for the formation an inclusive institutional environment. Noted that when foreign institutions importing and implementing it is important adopt them to the national conditions. Based on the accumulated international experience, has proposed practical measures to develop an inclusive institutional environment in the country.